Pro-angiogenic New Chloro-Azaphilone Derivatives From the Hadal Trench-Derived Fungus Chaetomium globosum YP-106 - Yaqin Fan; Chunjiao Jiang; Yan Zhang; Zhiheng Ma; Peihai Li; Lizhong Guo; Ting Feng; Liman Zhou; Lili Xu (Frontiers in Microbiology, 2022)
Five new chloro-azaphilones, chaetofanixins A–E (1–5), and five known analogs (6–10) were isolated and identified from the hadal trench-derived fungus Chaetomium globosum YP-106. The structure of chaetofanixin E (5) is unique and interesting, bearing a highly rigid 6/6/5/3/5 penta-cyclic ring system, which is first encountered in natural products. The structures of these compounds, including absolute configurations, were determined based on the spectroscopic analysis, electronic circular dichroism (ECD) calculations, and analysis of biogenetic origins. Compounds 1–7 significantly promoted angiogenesis in a dose-dependent manner, and thus, these compounds might be used as promising molecules for the development of natural cardiovascular disease agents.